Efektivitas Sistem Informasi Keuangan Daerah Terhadap Kinerja Pegawai: Dysfunctional Behavior Sebagai Variabel Moderating (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Banyumas) - Sudjono, Sudjono; Primasari, Dona; Sriwulandari, Ratu Ayu (Jurnal Manajemen Bisnis, 2014)
This study examines the relationship of Information Financial Systems to Officer performance:Dysfunctional Behavior as Moderating Variable. This research represents the empirical test which used sensus sampling technics in data collection. Data were collected using a survey of 101 from officer in local govermment of Banyumas Center of Java, Indonesia. Data analysis uses SPSS ver.18. Result of hypothesis examination indicate that from two hypothesis raised are Accepted.. Accepted fist hypothesis: there are positive influence between implementation of Government Information Financial System (SIKD) to Officer performance. Second hypotesis there are positive influence between implementation of Government Information Financial System (SIKD) to Officer performance mediated by dysfunctional behavior.